(untitled) (مجلة ديالى للبحوث الانسانية, 2023)
This study investigates and assesses the process of constructing the English language ministerial examinations at the preparatory schools in Iraq. It presents an analysis of samples of the Baccalaureate examinations. Data analysis showed that these examinations have neglected assessing learners’ ability to communicate orally. It is suggested that the questions have to be balanced paying more attention to the communicative language learning. Consequently, the researcher proposes an examination programme based on the principles of the communicative approach which prioritizes the development of the oral / aural language skill (communication) to bridge the gap in the current ministerial examinations at the preparatory schools. The proposed programme comprises both oral and written examinations in order to check learners’ achievement and performance in all four language skills, mainly in spoken and written language.